THE ROLE OF KNOWLEDGE IN PREVENTING MALARIA INCIDENCE AMONG PADDY FARMERS IN NORTHERN MALAYSIA - Nurul Syazwani Ahmad Sabri; Siti Noorjannah Abd Halim; Wan Aishah Wan Mohd Nowalid; Marziah Zahar, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The agriculture sector is notoriously associated with hazardous activities and high occupational accident rates, with most studies focusing on physical and chemical hazards. Biological hazards including zoonoses have been less studied due to scarce information and diverse perplexing factors that hinder the development of risk assessment activities by safety professionals. Zoonotic malaria, a communicable disease, has recorded upsurge in the infection rates in Malaysia. Malaria, a mosquito-borne infectious disease, poses significant risks to individuals working in agricultural settings, particular paddy farmers. Paddy farmers are highly vulnerable to these diseases due to their exposure to working environments such as stagnant water in the paddy field. This study aims to explores the relationship between the role of knowledge about malaria in preventing the incidence of malaria, highlighting the specific occupational challenges encounter by paddy farmers in Northern region of Malaysia. We propose the hypothesis that enhanced knowledge and awareness among paddy farmers about malaria and its prevention can contribute to notable reduction in the incidence of malaria. To test this hypothesis, we will conduct a questionnaire survey which will be distributed to collect data from selected paddy farming communities. The survey will evaluate the current level of knowledges associated with malaria prevention. The result of this study will provide valuable insight into the role of education and knowledge dissemination in alleviating biological hazards, with a main focus on malaria among the paddy farmers. Moreover, this research could contribute to the refinement of policy and practical interventions focusing in improving occupational health and safety of agricultural communities, ultimately boosting health outcomes and declining occupational accident rates.